2002
DOI: 10.1016/s0022-5347(05)65294-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predisposing to Urinary Tract Infection After J Ureteral Stent Insertion

Abstract: The risk of bacteriuria and colonization of the J stent tip is significantly enhanced by the duration of stent retention, patient sex and the systemic disease, such as diabetes mellitus, chronic renal failure and diabetic nephropathy. These categories of patients should undergo shorter stent retention, antimicrobial prophylaxis and careful followup to minimize infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
64
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 16 publications
6
64
0
1
Order By: Relevance
“…Also, there was a statistically significant difference depending on dwell time and comorbidi-ties; the diabetics and the patients with dwell time in excess of 90 days had significantly more positive urine cultures (6.8% vs. 28.6%, p value 0.01), as anticipated by previous published data [14] Stents left in situ more than 90 days have more than 9 times the chance of encrustations compared to their counterparts dwelling less than 30 days (76.3% vs. 8.5%).…”
Section: Discussionsupporting
confidence: 82%
“…Also, there was a statistically significant difference depending on dwell time and comorbidi-ties; the diabetics and the patients with dwell time in excess of 90 days had significantly more positive urine cultures (6.8% vs. 28.6%, p value 0.01), as anticipated by previous published data [14] Stents left in situ more than 90 days have more than 9 times the chance of encrustations compared to their counterparts dwelling less than 30 days (76.3% vs. 8.5%).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Kehinde et al [12] showed that the duration of J stent retention affects the rate of positivity of urinary cultures and J stent colonization, with a rate of 28.6 and 64.9%, respectively, with a stent indwelling time of 191 days; moreover, this author reports a bacteriuria rate in patients with no systemic disease that was significantly lower than in patients with diabetes mellitus, chronic renal failure and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 75%
“…Kehinde et al [13] showed that the risk of bacteriuria and colonisation of the J stent tip is enhanced significantly by a longer duration of stent retention, female gender, and systemic diseases such as diabetes mellitus, chronic renal failure and diabetic nephropathy and concluded that these categories of patients should undergo shorter stent retention, antimicrobial prophylaxis, and careful follow-up to minimise infectious complications. Coskun et al [14] stressed that early removal of the stent, 2 weeks after renal transplantation, decreased the rate of urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%